The reigns of Saul, David and Solomon with and without the letter 'h': academic and poetic translations of De aetatibus mundi et hominis’ Book VIII by Fulgentius the Mythographer - Santos Júnior, Cristóvão (Romanitas - Revista de Estudos Grecolatinos, 2021)
Following my gradual translation project of De aetatibus mundi et hominis by Fulgentius, I carried out the first two translations of his Book VIII into Portuguese. In this sense, I propose a academic alipogrammatic translation and a poetic lipogrammatic translation. The academic version emphasizes the semantic prism of the work, being useful to researchers who only seek to allude to Fulgentius’ thought. The poetic version, in turn, emphasizes the formal dimension of writing, avoiding, similarly to the Latin text, words that present the letter 'h'. Thus, I also seek to provide the reader with some opportunity for poetic enjoyment. In this section, the age pictured corresponds to the reigns of Saul, David, and Solomon, with many references to the Bible, which I flagged in the scholarly translation notes. I indicate again some general elements of De aetatibus, with the scope of directing the public that is still unaware of my work to read the pertinent bibliography, which I also do with my translations of the Ausonius and Fulgentius’ works. Then, I point out certain aspects of the translated Book. Finally, I use once again the critical edition fixed by Rudolf Helm (1898).
Keywords: Late Antiquity; Hebrew Monarchy; Fulgentius; Lipogram; Constrained Writing